Pengembangan E-LKPD Berbasis Website Wizer.Me Materi Teks Cerita Fantasi Kelas VII - Fransiskus Dwi Anggoro (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This study aims to describe the stages of developing E-LKPD based on the Wizer.me Website on fantasy story text material for class VII and the form of E-LKPD based on the Wizer.me Website on fantasy story text material for class VII. This research uses the Research and Development (R&D) method with the Borg and Gall model, which uses 6 stages according to the needs, abilities and scope of the research. The results of the study show that 1) the stages of developing E-LKPD based on the Wizer.me Website for fantasy story text material start from the potential and problem analysis stages with unstructured interviews with teachers and analysis of the LKPD used by the teacher during learning. The next stage is needs analysis, product design stage, product validation stage carried out by material expert validators and media design expert validators. The score obtained was 86.11% from the material expert validator, and 83.33% from the media design expert validator. Based on the results of this assessment, it can be concluded that the E-LKPD based on the Wizer.me Website, fantasy story text material for class VII "very feasible." ” is used in learning. The next stage is product revision, and finally the final product. The final product produced is in the form of an E-LKPD which is included on the Wizer.me Website which can be accessed using a device, laptop or computer via the link provided. 2) the form of this E-LKPD is in the form of an interactive multimedia LKPD which can be accessed via a link and will be transferred to the Wizer.me Website, this form of E-LKPD consists of the cover of the E-LKPD, KD and IPK, completion time, brief materials, work instructions -LKPD, and tasks that must be done.